Postgender Fiqh: The Views of MUI’s and KUPI’s Ulema on Postgenderism from Maqāṣid Sharī’ah Perspective - Iffatin Nur; Reni Puspitasari (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2023)
This study aims to formulate the paradigm of fiqh (Islamic law) in predicting various impacts of postgenderism by exploring postgender preferences according to MUI (Indonesian Council of Ulema) and KUPI (Indonesian Women Ulema Congress) scholars. This qualitative research begins with examining the perceptions of ulema (Muslim scholars) of both organizations regarding postgenderism. Primary data about perceptions and preferences on postgenderism were explored through in-depth interviews with four ulema, two from each organization. Secondary data were obtained through literature exploration from primary books and articles on postgender. Data analysis techniques employed spiral analysis equipped with content, comparative, and critical analysis. The findings show that: 1) based on maqāṣid sharī'ah (Islamic laws’ objectives), the ulema view that postgender ideologies and movement threaten human existence and risk the establishment of ḥifẓ al-dīn, ḥifẓ al-nasl and ḥifẓ al-‘irḍ (preserving one’s religion, offspring, and dignity respectively) and 2) postgenderism is considered as an ideology that allegedly violates sunnatullah (God’s laws) and threatens human existence and humanity. Therefore, every activity, facility, infrastructure, and opportunity born from it that threatens the existence of humanity must be avoided as much as possible. One of the preventive paradigms against postgenderism is formulated through uṣūl fiqh iftirāḍi (preventive Islamic law’s fundament) method as an anticipatory ijtihād (intellectual exercise) towards its various possible harms.